Approximate resolution of asynchronous conflicts among sequential collaborations in dynamic virtual environments. (4th July 2015) - Lee, Jun; Lim, Mingyu; Park, SungJun; Kim, HyungSeok; Ko, Heedong; Kim, Jee‐In
Abstract: Asynchronous collaboration for a networked virtual environment (NVE) has emerged as a promising area in collaborative computer‐aided design applications. The concept of asynchronous collaboration is a sequential collaboration of temporal processes in an NVE where the participants are not required to be present at the time of the collaboration. Conflicts in asynchronous collaboration occur because the preceding task of a participant can influence the output of the ensuing task of another participant. The conflicted tasks must be modified manually. However, it requires considerable time and effort to resolve conflicts in a sequential collaboration. In this paper, we present an asynchronous collaborative framework that converts the conflict states of the shared objects into approximately resolved states. We develop a novel approximate resolution algorithm using a task‐based modeling mechanism to resolve the asynchronous conflicts with their corresponding tasks. Moreover, we propose a visual relation editor for convenient management. The participants can set flexible relations among shared objects using the proposed visual editor. The proposed approximate resolution approach can significantly reduce the average resolution time and the number of required manual task resolutions in a virtual environment compared to a manual resolution approach. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Our primary objective is to provide a semi‐automatic resolution of the asynchronous conflicts using the relations of the affected objects. We develop a novel approximate resolution algorithm using a task‐based modeling mechanism to resolve the asynchronous conflicts with their corresponding tasks. The participants can set flexible relations among shared objects. Following the setting of the relations, the proposed system detects asynchronous conflicts of the shared objects and resolves the conflicts automatically according to the predefined relations.